Liver three-dimensional cellular models for high-throughput chemical testing - Yang, Shu; Ooka, Masato; Margolis, Ryan Jared; Xia, Menghang (Cell reports methods, 2023)
Drug-induced hepatotoxicity is a leading cause of drug withdrawal from the market. High-throughput screening utilizing in vitro liver models is critical for early-stage liver toxicity testing. Traditionally, monolayer human hepatocytes or immortalized liver cell lines (e.g., HepG2, HepaRG) have been used to test compound liver toxicity. However, monolayer-cultured liver cells sometimes lack the metabolic competence to mimic the in vivo condition and are therefore largely appropriate for short-term toxicological testing. They may not, however, be adequate for identifying chronic and recurring liver damage caused by drugs. Recently, several three-dimensional (3D) liver models have been developed. These 3D liver models better recapitulate normal liver function and metabolic capacity. This review describes the current development of 3D liver models that can be used to test drugs/chemicals for their pharmacologic and toxicologic effects, as well as the advantages and limitations of using these 3D liver models for high-throughput screening. In this review article, Yang et al. discuss the current status, challenges, and future promise of three-dimensional liver models for drug development and safety testing. They highlight the implications of cell types from different sources and several 3D culturing approaches for physiologically relevant modeling and high-throughput chemical testing.